Impact of a New Medical Record System for Emergency Departments Designed to Accelerate Clinical Documentation. Issue 26 (July 2015) - Inokuchi, Ryota; Sato, Hajime; Iwagami, Masao; Komaru, Yohei; Iwai, Satoshi; Gunshin, Masataka; Nakamura, Kensuke; Shinohara, Kazuaki; Kitsuta, Yoichi; Nakajima, Susumu; Yahagi, Naoki; Grewal., Perbinder Singh
<x xml:space="preserve">Abstract</x> Abstract Recording information in emergency departments (EDs) constitutes a major obstacle to efficient treatment. A new electronic medical records (EMR) system focusing on clinical documentation was developed to accelerate patient flow. The aim of this study was to examine the impact of a new EMR system on ED length of stay and physician satisfaction. We integrated a new EMR system at a hospital already using a standard system. A crossover design was adopted whereby residents were randomized into 2 groups. Group A used the existing EMR system first, followed by the newly developed system, for 2 weeks each. Group B followed the opposite sequence. The time required to provide overall medical care, length of stay in ED, and degree of physician satisfaction were compared between the 2 EMR systems. The study involved 6 residents and 526 patients (277 assessed using the standard system and 249 assessed with the new system). Mean time for clinical documentation decreased from 133.7 ± 5.1 minutes to 107.5 ± 5.4 minutes with the new EMR system (P < 0.001). The time for overall medical care was significantly reduced in all patient groups except triage level 5 (nonurgent). The new EMR system significantly reduced the length of stay in ED for triage level 2 (emergency) patients (145.4 ± 13.6 minutes vs 184.3 ± 13.6 minutes for standard system; P = 0.047). As for the degree of physician satisfaction, there was a high degree of satisfaction in terms of the physical findings support system and the ability to capture images and enter negative findings. The new EMR system shortened the time for overall medical care and was associated with a high degree of resident satisfaction.